Observations on the consumption and dispersal of Phoenix canariensis drupes by the Grey-headed flying-fox (Pteropus poliocephalus) - Spennemann, Dirk HR (European Journal of Ecology, 2018)
Aided by their transplantability as adult plants, Phoenix canariensis and Washingtonia robusta palms have a long history as ornamental feature trees in urban settings. With their plentiful production of carbo-hydrate reach drupes, palms have become a major food source for the grey-headed flying-fox (Pteropus poliocephalus) during late autumn and early winter. This paper reviews the consumption of Phoenix canariensis and Washingtonia robusta drupes based on the field observations and a morphological and metric analysis of spat-out remains (‘ejecta’). Based on a review of the mastication mechanics of fruit consumption, the paper demonstrates that P. poliocephalus can be ruled out as a disperser of the invasive Phoenix canariensis, but must be considered for the dispersal of Washingtonia robusta.